Balance and Self-efficacy of Balance in Children with CHARGE Syndrome. (July 2013) - Haibach, Pamela S.; Lieberman, Lauren J.
Introduction: Balance is a critical component of daily living, because it affects all movements and the ability to function independently. Children with CHARGE syndrome have sensory and motor impairments that could negatively affect their balance and postural control. The purpose of the study presented in this article was to assess the balance and self-efficacy of balance of these children. Methods: Twenty-one children with CHARGE syndrome aged 6-12 and 31 age- and gender-matched sighted control participants without CHARGE syndrome completed the study. Each participant completed the Pediatric Balance Scale (PBS) and a self-efficacy of balance survey, the Activities-Specific Balance Confidence Scale (ABC). Results: The PBS results revealed that the participants in the control group performed significantly better than did those with CHARGE syndrome (p < .05), with 57% of those with CHARGE syndrome at a medium to high risk of falls but all those in the control group at a low risk. Most children with CHARGE syndrome also had low ABC scores, and these scores were moderately correlated with the PBS scores (r = 0.56), but were not significantly associated with gender (r = 0.065) or age (r = −0.169). Discussion: A relationship was found between the balance self-efficacy of the children with CHARGE syndrome and their objectively measured balance. Self-efficacy of balance has been correlated with an increased risk of falls and with decreased participation in physical activities. Increased physical activity with a focus on balance and movement would likely improve these children's balance and self-efficacy of balance. Implications for practitioners: Practitioners should understand that children with CHARGE syndrome will likely have poorer balance and lower confidence in their balance. Balance confidence and capabilities have implications for the development of motor milestones, such as walking, and the ability to perform functional activities. Future research should examine interventions to improve both balance and confidence in balance in these children.